Toward a Green Atom Economy: Development of a Sustainable Multicomponent Reaction - Garbarino, Silvia; Protti, Stefano; Basso, Andrea (Synthesis, 2015)
The recently discovered photoinduced three-component reaction of diazo ketones, carboxylic acids, and isocyanides can be efficiently performed under continuous-flow conditions with consequential advantages in terms of selectivity and productivity. The investigation of the flow process and the determination of its sustainability are discussed in detail. This multicomponent reaction affords stereodefined captodative olefins, useful as synthons in organic chemistry.
Keywords: multicomponent reactions; photochemistry; flow chemistry; green chemistry; diazo compounds; isocyanides